In ovo Vaccine Against Infectious Bursal Disease - Moura, L.; Vakharia, V.; Liu, M.; Song, H. (International Journal of Poultry Science, 2007)
A recombinant attenuated vaccine against infectious bursal disease virus (IBDV) was administered in ovo to 18-day-old embryos. The vaccine was genetically tailored to protect from challenges in the field against classic and variant strains of IBDV. The vaccine virus contains neutralizing epitopes from both classic (D78) and variant strain (GLS), and abrogates expression of the nonstructural protein, VP5 of IBDV. Specific-pathogen-free (SPF) and fertile broiler eggs obtained from a local poultry farm were vaccinated and used to evaluate protection against IBDV-STC challenge. A full dose of the vaccine consisting of 5.6x103 plaque forming units (pfu) was administered to SPF and broiler embryos. In addition, a half dose of the vaccine containing 2.3x103 pfu 21 pfu 21 was injected into SPF embryos. The vaccine had no effect on hatchability or first week survival in either broilers or SPF birds, even when high doses were administered. The vaccine generated high antibody titers in chickens with either dosage. All vaccinated groups were protected against mortality. The vaccine did not cause bursal damage and fully protected SPF chickens vaccinated in ovo with half dose of the vaccine and broiler chicks that received a full dose of the recombinant vaccine in ovo.